2007
DOI: 10.1097/01.olq.0000253375.59976.24
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Genital Chlamydial Infection Among Male Patients Attending an STD Clinic in Taipei, Taiwan

Abstract: C. trachomatis genital infection was prevalent among male patients attending a STD clinic in Taipei. Young Taiwanese men attending STD clinics should be counselled on condom use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Overall, the most prevalent genotypes detected in this study were F (25.6z), E (17.1z), and J (16.3z). This C. trachomatis genovar distribution pattern is similar to the patterns that have been reported among male patients in Guangdong province (6,7) and Taiwan (12), female sex workers in southern China (13), prostitutes and non-prostitutes in Thailand (14) as well as female patients in Japan (15). These genovars may be the most prevalent circulating in Asia (14,15), and possibly the world (16).…”
supporting
confidence: 58%
“…Overall, the most prevalent genotypes detected in this study were F (25.6z), E (17.1z), and J (16.3z). This C. trachomatis genovar distribution pattern is similar to the patterns that have been reported among male patients in Guangdong province (6,7) and Taiwan (12), female sex workers in southern China (13), prostitutes and non-prostitutes in Thailand (14) as well as female patients in Japan (15). These genovars may be the most prevalent circulating in Asia (14,15), and possibly the world (16).…”
supporting
confidence: 58%
“…Lastly, 50% of chlamydia-positive specimens were able to be sequenced, lower than in previous studies. 16,60 The main reason may be due to low chlamydial load in the original urine specimen from an asymptomatic infection, and degradation of the targeted ompA DNA over the one-year 2808C freezer storage.…”
Section: Discussionmentioning
confidence: 99%
“…6 -14 Limited genotyping data in Taiwan indicated that serovar E was the most common serovar, followed by serovar F in sexually transmitted disease (STD) clinic patients. 15,16 Therefore, we designed this study to determine: (i) the prevalence of both non-sexual risk-taking behaviours and sexual behaviours in Taiwanese teenagers using the AORT-CASI approach; (ii) the prevalence of C. trachomatis and N. gonorrhoeae infections by NAATs; (iii) the distribution of C. trachomatis serovars; and (iv) the association between sexual risk behaviours and infection.…”
Section: Introductionmentioning
confidence: 99%